Let’s be a chef! The antecedents of chef’s key competencies for vocational school students - Lastariwati, Badraningsih; Mahfud, Tuatul (Institute of Advanced Engineering and Science, 2025)
Chefs are considered a factor in the success of a culinary tourism business. Therefore, mastering the chef’s key competencies (CKC) through vocational high schools is very important. Many studies have examined the competence of chefs. Still, the mechanism for getting key competency chefs involving industry commitment (IC), social support (SS), vocational teaching quality (TQ), and occupational self-efficacy (OSE) of culinary student chefs has not been discussed clearly. This study investigates the antecedents of the mastery of key chef competencies for vocational school students. This study involved 392 culinary students at seven vocational schools in Yogyakarta, Indonesia. Data was collected by proportional random sampling through a questionnaire. Amos 18 software is used for structural equation modeling (SEM) analysis. The study’s results revealed that the mastery of the chef’s critical competencies for students was directly and significantly influenced by IC, quality of vocational teaching, and OSE of chefs. In addition, chef OSE is a mediator on the influence of IC, SS, and quality of vocational teaching on mastering the chef’s critical competencies for culinary students. This study’s findings discuss in depth some of the implications for vocational education practitioners that are proposed for further improvement.